M MEMAHAMI HAKEKAT KEPRIBADIAN MUSLIM DAN PEMBENTUKANNYA MELALUI PENDIDIKAN DALAM ISLAM - AYU DEVI SETIOWATI (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
In essence personality does not occur immediately but is formed through a very long life process, while the target to be addressed in personality formation is personality having noble character. The level of moral nobility is closely related to the level of faith. Therefore the Prophet Muhammad S.A.W said that